(untitled) (Archives of Pediatrics of Uruguay, 2025)
Introduction: the practice and duration of breastfeeding are subject to modifications due to social, economic and cultural influences. Objectives: analyze from a critical historical perspective the process underway in Uruguay regarding the recommendations, characteristics and evidence that support breasfeeding practices. Methodology: we systematized the search in national libraries and repositories. A documentary review of recommendations on the duration of breastfeeding issued in Uruguay between 1970 and 2023 was carried out. They were classified according to type, origin, structure, authors, time and frequency of publication. We excluded international and national documents of general dissemination, undergraduate or graduate theses. Results: 109 documents were obtained. More than a third include publications generated by the state, followed by case studies and technical guidelines. The largest number of documents was published between 2000 and 2019, coinciding with the generation of international scientific evidence. There is a transition in the recommendation of total duration ranging from 12 months, from 12 to 24 months and from 24 months and more, with controversies at national level and regarding international positions. Conclusions: the recommendations on breastfeeding duration in Uruguay have a strong medical, nutritional and public health imprint, There is a lack of participation of psychology, neurosciences, child development, and other human behavioral sciences, with a gender perspective. This review enables us to gain perspective and to problematize the results, to achieve a more comprehensive approach to the total duration of breastfeeding.